IDENTIFIKASI SENYAWA AKTIF ANTIFEEDANT DARI EKSTRAK DAUN PANGI (Pangium Sp) DAN UJI AKTIVITASNYA TERHADAP ULAT KUBIS (Plutella Xylostella) - Ida Bagus Putra Mahardika; Ni Made Puspawati; Ida Ayu Gede Widihati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
Leaves of pangi (Pangium edule) are known to have many benefits, including antifeedant activity. 500 g of pangi leaf powder was extracted by maceration method using n-hexane extract yieled 4.51 g of dark green extract. This extracts showed high antifeedant activity (47.23%) against Plutella Xylostella at a concentration of 0.1% (w / v). Separation of 2 g of n-hexane extract by chromatography column using n-hexane: ethyl acetate: chloroform (6:2,5:1,5) as mobile phase and silica gel 60 as stationary phase produced 6 groups of fractions. Fractions 3 reveiled the highest antifeedant activity that is 52.15%, 69.88%, and 91.66% respectively at a concentration of 10 ppm, 100 ppm, and 1000 ppm. This active fraction which was considered relatively pure following purity test on TLC was then identified using GC-MS spectrometre. GC-MS spectra of antifeedant active compound contained at least 11 compounds with 8 compounds successfully identified as ? – pinene, benzene trimethyl, acetic acid triflouro-tetradecyl ester, nonadecene, 13-Hexyloxacyclotridec-10-en-2-one, phytol, 3-eicosene, , benzenedicarboxylic acid diisooctyl este.